Comparing the Effectiveness of Multitask Role-play and Traditional Technique in Teaching Speaking to Students with Different Self-Confident Levels - Siti Nurhayati; Rudi Hartono; Rahayu Puji H (Universitas Negeri Semarang, 2023)
In English education, speaking skills are very crucial developed, because it plays essential roles in communication. Based on the research at SMP Al Falah, multiple problems might have taken place concerning the teaching and learning of speaking skills. One was the traditional technique that made the learning process run monotonously and boring. Besides that, many students still needed help, such as they answered with many lexico-grammatical mistakes and ideas required to speak up. They also needed to be more confident. Therefore, this research applied to multitask role play, it is the role-play technique combined with activities or tasks which allow the students to get exposed to authentic models from youtube, communicate with each other, and solve a problem or complete a task. In this case, the writers figured out that this role play used authentic materials as models that can be taken from the internet, such as the videos from